RANGKEP DALAM KARAWITAN JAWA : STUDI KASUS RICIKAN KENDANG - Sigit Setiawan; Supardi Supardi; Sukamso Sukamso (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
This paper is based on the idea that the term deep musical used in Javanese karawitan is also the daily term of the Javanese people. One of them looks at the concept of duplicate. This concept is seen from the point of view of the musicality of the drums. The theory used to reveal the dual concept is the Schutz approach which views humans as "self-elucidation" or "self-explanation," which, in carrying out research, explores more: what they say, what they think, and what they interpret about their world. (Walsh and Wals, 1967). "They," in the context of Schutz, are musicians, especially musicians in Surakarta. A literature review of several writings related to drums was carried out in this study. The method used is qualitative with a descriptive analysis approach. The results of this study suggest several things; the existence of sekaran rangkep in the vocabulary kendang, sekaran rangkep can also involve sekaran ciblon gambyong, the existence of singgetan rangkep, and proving that rangkep is more inclined to one garap rather than stating one level of rhythm.